(3RjGOI GdLGeY GdUZjQ aj CMGOjK GdHTjQ GdfPjQs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s ((3eMeO Hf YHO GdLdjd GdTGaYi GdHOQGfi s)
(3ChdgG (B:s
(3GdMeO ddg Ydi CaVGdg gPG Pjd Ydi cJGHi GdeSei HGdLGeY GdUZjQ ef MOjK GdHTjQ GdfPjQ , SejJg HRjGOI GdLGeY , hQehQg cQehRg , hGdJQJjH cGdJQJjH s
(3BNQgG (B:s
(3GdjSQ jef hGdYSQ The aQYf QLd Je GdcJGH s
(3HgG fXGe GdJYbjHIs
(3cJHJ Chd GdCMGOjK hGdQehR HGdCMGOjKs
(3Ydi GdfSNI JbjjOGJ s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs